If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12=n-9n=
We move all terms to the left:
12-(n-9n)=0
We add all the numbers together, and all the variables
-(-8n)+12=0
We get rid of parentheses
8n+12=0
We move all terms containing n to the left, all other terms to the right
8n=-12
n=-12/8
n=-1+1/2
| (6x)=18 | | 90=5(x+11) | | 4x-3x+18=-x | | (x+4)=-10 | | 32=2(x+7)+2(2x-3) | | X=1+5i | | 2y+2y+3y-4y=15 | | 3x2-x+7,x=1 | | (3x-3)=-9 | | 2y+2y+3y+4y=15 | | (3x-3)=9 | | 11+10x=2x+9 | | x÷4-4=5 | | -66+11x=24+14x | | 8(x)=2x+5 | | 8q+q-7q+2q+2q=6 | | 4z+3(4-z)=-(z-5)+3 | | 3.8x-2(x-9)=4.4x+5 | | (x+11)=2x-8 | | 3x+8x=84 | | 3x+8x=844 | | 2(x-5)=6(x-3) | | (x+6)=-7 | | -24-9x=-5x+56 | | 3x-5=5x+10= | | n+2n+30+40=2+3+4+5+6 | | 8(2x–1)–3(5x–3)=1 | | 8.36n+2.44=-2.17n+5.32 | | (4x-6)=-18 | | 4x/5-50=26 | | 3x+8x=204 | | 6x2-36+18=0 |